تكوين المحافظ الاستثمارية باستخدام نظرية الألعاب (دراسة تطبيقية على سوق دمشق للأوراق المالية) (Journal of Hama University, 2024)
The research aims to demonstrate the significance of game theory and its efficacy in resolving problems characterized by conflicting objectives and interests. These problems encompass the selection of an investment portfolio with two opposing goals: maximizing returns and minimizing risk. By employing linear programming to address this challenge, the study was applied to a sample of stocks listed on the Damascus Securities Market from 2013 to 2022.The research began with the mathematical formulation of the players' dilemmas. The optimal solution was then derived using the simplex method, facilitated by the Solver tool in Excel. Subsequently, the outcomes of each player's strategies were analyzed, encompassing portfolio calculation, risk assessment, and evaluation using Sharpe and Treynor measures.In comparison to the market portfolio, several noteworthy findings were obtained. Notably, the study showcased the capacity of game theory and linear programming to select an investment portfolio that simultaneously maximizes returns while minimizing risk. Furthermore, the performance of the matched portfolio, as measured by Sharpe and Treynor indicators, was found to be inferior to that of the market portfolio when adopting matched returns. However, when considering expected returns, the matched portfolio exhibited superior performance compared to the market portfolio